Effects of substance P on spontaneous contraction in the flexure region of the guinea pig colon - Chowdhury, JU; Nahar, NS (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):17-9.The abstract of this article is available on the PubMed website